African cities and collaborative futures Urban platforms and metropolitan logistics - Keith, Michael; de Souza Santos, Andreza Aruska (Manchester University Press, 2021)
African cities and collaborative futures: Urban platforms and metropolitan logistics brings together scholars from across the globe to discuss the nature of African cities - the interactions of residents with infrastructure, energy, housing, safety and sustainability, seen through local narratives and theories. This groundbreaking collection, drawing on a variety of fields and extensive first-hand research, offers a fresh perspective on some of the most pressing issues confronting urban Africa in the twenty-first century. Each of the chapters, using case studies from Ethiopia, Kenya, Malawi, Niger, Nigeria, South Africa and Tanzania, explores how the rapid growth of African cities is reconfiguring the relationship between urban social life and its built forms. While the most visible transformations in cities today can be seen as infrastructural, these manifestations are cultural as well as material, reflecting the different ways in which the city is rationalised, economised and governed. How can we 'see like a city' in twenty-first-century Africa, understanding the urban present to shape its future? This is the central question posed throughout this volume, with a practical focus on how academics, local decision-makers and international practitioners can work together to achieve better outcomes.